2012
DOI: 10.5387/fms.58.144
|View full text |Cite
|
Sign up to set email alerts
|

INHIBITORY EFFECT OF ^|^beta;-HYDROXYBUTYRIC ACID ON L-TYPE Ca2+ CURRENT UNDER ^|^beta;-ADRENERGIC STIMULATION IN GUINEA PIG CARDIAC VENTRICULAR MYOCYTES

Abstract: : Severe ketoacidosis induces heart failure and cardiac arrest, but its mechanism is unknown. Recently, hydroxy -carboxylic acid receptor 2 (HCA 2 ) was found to be a receptor for a ketone body, β -hydroxybutyric acid (BHB), and is coupled with Gi -GTP binding protein. HCA 2 expression was reported in the guinea pig heart. Therefore, using guinea pig cardiac myocytes, we investigated effects of BHB on L -type Ca 2+ current pre -augmented with β -adrenoceptor agonist, isoproterenol under the whole -cell voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Some epilepsy patients may have abnormal transcellular membrane ion channels resulting in a predisposition to develop conduction abnormalities as seen in those who develop long QT on cisapride, tricyclics, or class I and III antiarrhythmics (Best et al, 2000). One study revealed that β-OHB at high concentrations (10 mM) reduced L-type Ca 2+ current in guinea pig ventricular myocytes but only in the presence of the β–adrenergic agonist isoproterenol, however it had no effect on L-type Ca 2+ current under basal conditions (Kurihara et al, 2012). Another study suggested that the L-stereoisomer of β-OHB could block the transient outward K + current ( I to ) in murine ventricular myocytes causing action potential prolongation (Doepner et al, 1997) while D-β-OHB had no effect.…”
Section: Role Of β-Ohb In Cardiovascular Health and Diseasementioning
confidence: 99%
“…Some epilepsy patients may have abnormal transcellular membrane ion channels resulting in a predisposition to develop conduction abnormalities as seen in those who develop long QT on cisapride, tricyclics, or class I and III antiarrhythmics (Best et al, 2000). One study revealed that β-OHB at high concentrations (10 mM) reduced L-type Ca 2+ current in guinea pig ventricular myocytes but only in the presence of the β–adrenergic agonist isoproterenol, however it had no effect on L-type Ca 2+ current under basal conditions (Kurihara et al, 2012). Another study suggested that the L-stereoisomer of β-OHB could block the transient outward K + current ( I to ) in murine ventricular myocytes causing action potential prolongation (Doepner et al, 1997) while D-β-OHB had no effect.…”
Section: Role Of β-Ohb In Cardiovascular Health and Diseasementioning
confidence: 99%